Biomechanics of the forehand stroke - Bahamonde, R. (coachesinfo.com)
Content: Introduction - Preparation - The Backswing - The Forward Swing - Racket Trajectory and Orientation - Linear and Angular Momentum Conclusion : What can coaches or players do to produce explosive forehands? Coaches and players need to understand the basic biomechanical principles and how to apply them to the different components of the strokes. There is no doubt that one of the most important sources of power for a tennis player comes from the racket. The new rackets not only allow the players to hit ball harder, they also provide more control. A firm grip near impact is necessary to control the racket during off-centre hits. Use a square stance whenever possible, it not only seems to be more effective in generating linear and angular momentum but it also seems to produce a more accurate racket path. Try to develop a smooth and continuous small-loop backswing. Select the forward swing (multi-segment or single unit forehand) that best suits the player's physical and motor skill abilities. Regardless of the type of forward swing, stress the importance of using trunk rotation and the legs throughout the forehand stroke and explain to the players the importance of a proper follow-through.